Pengaruh Jumlah Twist per meter (TPM) dan Rangkapan Benang terhadap Kinerja Mekanis Benang Gintir - Nurazizah, Verawati; Wijayono, Andrian; Rusman, Fahmi Fawzy; Ikhsani, Nurfadilah; Pradifta, Reski Alya; Murti, Wilda (Universitas Muhammadiyah Sorong, 2025)
Ply yarn is widely used in high-performance textiles due to its superior tensile strength and durability compared to single yarn. However, the selection of twist per meter (TPM) and the number of plies in ply yarn significantly influences its mechanical properties. This study aims to examine the effect of TPM and the number of plies on the tensile strength and elongation of ply yarn. An experimental approach was employed, varying TPM (550, 650, and 750 TPM) and the number of plies (2 and 3). Tensile tests were conducted to measure the yarn's tensile strength and elongation, while two-way ANOVA statistical analysis was used to evaluate the influence of each variable. The results indicated that TPM and the number of plies significantly affected the tensile strength and elongation of ply yarn (p < 0.05), while their interaction was not significant (p > 0.05). Increasing TPM enhanced tensile strength up to a certain limit before declining, whereas a higher number of plies improved both tensile strength and elongation but also increased yarn stiffness. These findings confirm that an optimal combination of TPM and the number of plies is essential to achieve the best balance between tensile strength and flexibility in ply yarn.